Mycosporine-like amino acids vs carrageenan yield in Mazzaella laminarioides (Gigartinales; Rhodophyta) under high and low UV solar irradiance. Issue 5 (1st September 2017) - Navarro, Nelso P.; Figueroa, Félix L.; Korbee, Nathalie
Abstract: The effects of increased solar photosynthetically active radiation (PAR) and ultraviolet radiation (UVR) on biomass, mycosporine-like amino acid (MAA) content, and carrageenan yield were studied for 14 days in tank-cultivated tetrasporophytes and gametophytes of Mazzaella laminarioides from the Magellan Strait. The initial values of carrageenan yield were similar between gametophytes and tetrasporophytes, whereas the MAA content was higher in gametophytes than that in tetrasporophytes. After 14 days of exposure to different combinations of solar radiation (PAR, PAR + UV-A, and PAR + UV-A + UV-B) and two irradiance levels (high and low), differences between gametophytes and tetrasporophytes of M. laminarioides in growth rate (GR), MAA, and carrageenan yield were observed. Higher GRs were observed in gametophytes than in tetrasporophytes under all radiation and irradiance treatments. A significant decrease in total MAA content was observed in both reproductive phases, with these decreases being more evident in gametophytes under all radiation and irradiance treatments (20 to 30% decrease compared with the initial value). Changes in the proportion of each MAA were also observed. The asterina-330 and palythine content decreased in gametophytes in all radiation and irradiance treatments, whereas tetrasporophytes exhibited an increase of these MAAs, mainly under PAR + UV-A at low irradiance. The carrageenan yield decreased in tetrasporophytes in all radiation treatments, whereas gametophytes exhibited an increase in this parameter under UV radiation at high irradiance. These results suggest that both reproductive phases have different strategies to cope with light stress, mainly under high UVR. Furthermore, both reproductive phases are adapted to high solar radiation, and the differences between gametophytes and tetrasporophytes could result from the vertical distribution on shore and from intrinsic differences related to ploidy level.